Violence workers : police torturers and murderers reconstruct Brazilian atrocities - Huggins, Martha Knisely, 1944-; Haritos-Fatouros, Mika, 1930-2014; Zimbardo, Philip G. (University of California Press, 2002)
Of the 23 Brazilian policemen interviewed in depth for this landmark study, 14 were direct perpetrators of torture and murder during the three decades that included the 1964-1985 military regime. The policemen help answer questions that haunt today's world.
Keywords: Police brutality -- Brazil.; Political atrocities -- Brazil.; Torture -- Brazil.; Brutalités policières -- Brésil.; Atrocités politiques -- Brésil.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Police brutality; Political atrocities; Torture; Brazil; Geweld.; Martelen.; Politie.; Psychologische aspecten.; Brazilië; Casestudies (vorm)